Stunting Prevalence and Human Development Index Using a Spatial Approach in West Java in 2021 - Utami, Gea Puteri; Rahmaniati, Martya; Bagus, Nurzahara (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Stunting is a recognized growth and development disorder in children that has long-term impacts such as mental retardation, low learning ability, and the risk of chronic disease. According to the World Bank (2016), stunting can cause long-term economic losses of 2-3% (potential losses of IDR 260 trillion - IDR 390 trillion per year). West Java is one of the most populous provinces in Indonesia (49.5 million people in 2023), with a high stunting rate of 24% (2021), above the national average. This study aims to examine the prevalence of stunting and the Human Development Index in regencies and cities in West Java Province in 2021 descriptively using a geographic information system (GIS) application.